Hormona liberadora de gonadotropina en toros de raza Brahmán sobre los parámetros reproductivos - Trujillo Pionce, Kevin Xavier (2024)
The purpose of this study was to evaluate the use of gonadotropin releasing hormone (GnRH) in Brahman bulls on their reproductive parameters. For its accomplishment, an experimental study of longitudinal approach was developed, in which 8 bulls from six to ten years of age were evaluated and submitted to five treatments, where T0: 0ml GnRH (initial parameters), T1: 2ml GnRH (Day 0), T2: 4ml GnRH (Day 30), T3: 6ml GnRH (Day 60) and T4: 8ml GnRH (Day 90). The review of their variability was developed using a completely randomized design (CRD) under assumptions of normality (Shapiro Wilks) and analysis of variance (Anova) and (Kruskal Wallis), complemented with the Tukey test (Tukey) at 5% for verification of significance. The results show that T4 with the use of 8 ml of GnRH presents better parameters with levels of significance lower than (p<0.005), the average scrotal circumference was 46.56 cm, the volume of ejaculate reached 9.63 ml, and the sperm concentration was 453 million spermatozoa per ml ejaculate, in addition, the mass motility was maintained on a scale of 4. 25, with 66.25% progressive motility, 73% sperm normality was recorded, and a better libido was observed with a scale of 4. Additionally, it is presented as an economically viable treatment with a net benefit of $1,986.72, due to the higher number of straws obtained. The findings suggest that high doses of GnRH (8ml) improve andrological parameters in bulls.